Hyperprolactinemia in infertile women - Salinas, Joel (2015)
OBJECTIVES: To identify the characteristics of patients with infertility and hyperprolactinemia (HPRL). METHOD: 464 medical records of 39 women Infertility Service of Archbishop Loayza (HAL) Hospital were reviewed; selected which had at least two dosages of prolactin (PRL) levels greater than 25 ng / ml, aged between 15 and 42 years, while infertility> 1 years and sexually active. RESULTS: Patients with HPRL represent 8.4% of infertile women HAL. Of these, 56.4% had PRL between 26 and 50 ng / mL; average age of 33.1 years and 5.4 years time disease. The most relevant antecedents were: abortion (48.7%), galactorrhea (35.9%), menstrual disorders (25.6%), unsatisfactory sex (23.1%) and exercise (23.1%). The most important clinical findings were: galactorrhea (46.2%), BMI> 25 mass (44.8%) and inadequate luteal phase (43.6%). The most common etiologic diagnoses were idiopathic HPRL (53.8%) and physiological (20.5%). Patients with pituitary microadenoma had significantly higher levels than women with other etiologies of HPRL (p <0.05) PRL. CONCLUSIONS: The prevalence of HPRL in infertile patients was lower than expected. The patients came late HPRL medical help.